Insecticidal Activity of Local Plants Essential Oils Against Laboratory and Field Strains of Anopheles gambiae s. l. (Diptera: Culicidae) From Burkina Faso - Wangrawa, Dimitri Wendgida; Badolo, Athanase; Ilboudo, Zakaria; Guelbéogo, Wamdaogo Moussa; Kiendrébeogo, Martin; Nébié, Roger Charles Honorat; Sagnon, N'Falé; Sanon, Antoine (Journal of economic entomology, 2018)
The emergence and intensification of resistance to insecticides in malaria vector populations is the main obstacle to insecticide-based control efforts. The main objective of this study was to evaluate the larvicidal and adulticidal properties of the essential oils (EOs) of Ocimum canum, Hyptis suaveolens, Hyptis spicigera, and Lantana camara on field-collected, pyrethroids-resistant mosquitoes, local laboratory strains, and susceptible ‘Kisumu’ strain of Anopheles gambiae (Meigen) (Diptera: Culicidae) populations. Larvae and adults of these mosquitoes were challenged against four EOs. The mortality rates of larvae and adults were assessed 24 h after exposure to the EOs. Species identifications and detection of the L1014F and L1014S kdr mutations and the 1575Y super-kdr mutation were carried out using polymerase chain reaction on the pyrethroid-resistant mosquitoes from the field. EO compositions were analyzed by gas chromatography and mass spectrometry. Monoterpene hydrocarbons were the major components of H. suaveolens and H. spicigera EOs (49.8%) and (69.6%), respectively, whereas oxygenated monoterpenes (68.7%) were predominant in the O. canum EO. For L. camara, the component yields were variable, but it was the most effective EO against all strains. The LC50 values for the larvae were 7.73 and 25.63 ppm for the susceptible ‘Kisumu’ and resistant field strains, respectively. The LC50 for adults was 0.24% for the susceptible strain and 1.98% for the resistant strain. Molecular analysis confirmed the presence of L1014F and N1575Y mutations in resistant Anopheles arabiensis and Anopheles coluzzii mosquitoes from the field. Our results highlighted the potential of the EOs of local plants as insecticides against resistant and susceptible strains of An. gambiae populations.